1997
DOI: 10.1136/jnnp.62.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Is 11C-flumazenil PET superior to 18FDG PET and 123I-iomazenil SPECT in presurgical evaluation of temporal lobe epilepsy?

Abstract: Objective-To determine the contribution of 58FDG PET, "IC-flumazenil PET, and 123I-iomazenil SPECT to the presurgical evaluation of patients with medically intractable complex partial seizures. Methods-Presurgical evaluation was performed in 23 patients, who were considered candidates for temporal lobe resective surgery (14 females and nine males with a median age of 34 (range 13 to 50) years).The presurgical diagnosis was based on seizure semiology as demonstrated with ictal video recording, ictal and interic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 17 publications
(18 reference statements)
4
55
1
1
Order By: Relevance
“…47 One study reported results for all patients included in the study and also allowed results to be extracted separately for patients in whom EEG localised the seizure focus. 40 This study reported very similar results for both sets of data. A second study reported data for two different tracers: IDEX and HMPAO.…”
Section: Interictal Spectsupporting
confidence: 76%
See 4 more Smart Citations
“…47 One study reported results for all patients included in the study and also allowed results to be extracted separately for patients in whom EEG localised the seizure focus. 40 This study reported very similar results for both sets of data. A second study reported data for two different tracers: IDEX and HMPAO.…”
Section: Interictal Spectsupporting
confidence: 76%
“…40 Another study also reported results separately for two different tracers [␣-methyl-L-tryptophan (AMT) and FDG]. 58 A further study reported results for two methods of interpretation of the PET scans: visual and statistical parameter mapping (SPM) analysis.…”
Section: Figure 15 Volumetric Mri: Forest Plots For Each Localisationmentioning
confidence: 96%
See 3 more Smart Citations